Assessing the Survival of the Redbay Ambrosia Beetle and Laurel Wilt Pathogen in Wood Chips - Don Spence; Jason Smith; Albert Mayfield; Jiri Huler; Randy Ploetz; Lukasz Stelinski (EDIS)
What is the best way for homeowners to dispose of dead redbay trees to avoid spreading laurel wilt? This 4-page fact sheet summarizes a UF/IFAS study providing evidence that a simple technique — chipping the dead trees — can help contain the disease within a small area and that there is a low probability of long-distance movement of LW via wood chips. Written by Don Spence, Jason Smith, Albert Mayfield III, Jiri Huler, Randy Ploetz, and Lukasz Stelinski, and published by the UF Department of School of Forest Resources and Conservation, November 2011. Reviewed August 2014.